2002
DOI: 10.1021/ol026231n
|View full text |Cite
|
Sign up to set email alerts
|

Thymidine 3‘,5‘-Diphosphoric Acid Derived Cations and Radicals:  Ab Initio Study

Abstract: The relative stabilities of thymidine-3',5'-diphosphoric acid (1) derived isomeric cations and radicals were calculated and key geometric parameters were thoroughly analyzed. The most probable sites of a hydride-ion (1', 2', 5-Me) and H-atom (4', 5', 5-Me) abstraction were identified, thus allowing prediction of the regioselectivity of potential damage to the deoxyribose ring and thymine moiety caused by carcinogenic agents of electrophilic and radical nature. [structure: see text]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 33 publications
(16 reference statements)
1
22
1
Order By: Relevance
“…Surprisingly, many modeled nucleosidic molecular backbones were assigned to the desired 2′-deoxyribose-associated cations, but they are not of those cations. The first non-empirical, low-accuracy study of nucleotide cations delivered incorrect conclusions. The obtained molecular structures were assigned to 2′-deoxyribose-localized carbocations.…”
Section: Resultsmentioning
confidence: 74%
“…Surprisingly, many modeled nucleosidic molecular backbones were assigned to the desired 2′-deoxyribose-associated cations, but they are not of those cations. The first non-empirical, low-accuracy study of nucleotide cations delivered incorrect conclusions. The obtained molecular structures were assigned to 2′-deoxyribose-localized carbocations.…”
Section: Resultsmentioning
confidence: 74%
“…The difference between the Gibbs free energies of the C1 0 -and C2 0 -centered radicals is found to be 8.0, 6.4, and 6.6 kcal/mol at the B3LYP/ AUG-cc-pVDZ, BHandHLYP/AUG-cc-pVDZ, and MP2/AUG-cc-pVDZ levels of theory in gas phase, respectively (Table III). Several previous gas phase theoretical studies [11,15,[18][19][20] have shown that the deoxyribose radicals centered at the C1 0 and C2 0 sites are most and least stable, while other gas phase theoretical studies [16,17] have shown that C4 0 -and C2 0 -centered deoxyribose radicals are most and least stable, respectively (Table III). As the molecules from which the radicals are derived and the levels of theory used are not the same [11,[15][16][17][18][19][20], a quantitative comparison of the results obtained in these studies cannot be made (Table III).…”
Section: Table IIImentioning
confidence: 96%
“…Several previous gas phase theoretical studies [11,15,[18][19][20] have shown that the deoxyribose radicals centered at the C1 0 and C2 0 sites are most and least stable, while other gas phase theoretical studies [16,17] have shown that C4 0 -and C2 0 -centered deoxyribose radicals are most and least stable, respectively (Table III). As the molecules from which the radicals are derived and the levels of theory used are not the same [11,[15][16][17][18][19][20], a quantitative comparison of the results obtained in these studies cannot be made (Table III). The difference between the Gibbs free energies of the most and least favored radicals obtained in the present study is close to that obtained in a previous study [19] and a similar information is also revealed by the zero-point energy (ZPE)-corrected total energies reported in another previous study [20].…”
Section: Table IIImentioning
confidence: 96%
See 1 more Smart Citation
“…Strong intramolecular interactions between nucleobases and the sugar ring take place in nucleoside cations as theoretical modeling shows for the 3′-dehydro derivative of thymidine 3′,5′-diphosphatethis cation has a cyclonucleoside backbone. 6 If similar tricyclic cations exist for CvO-protonated keto nucleosides, could they be responsible for the lability of the parent nucleosidic ketones? Herein, we examine this hypothesis by means of theoretical and synthetic models.…”
mentioning
confidence: 99%